MENINGKATKAN PEMAHAMAN MAJAS DALAM PUISI MENGGUNAKAN POWERPOINT INTERAKTIF PADA KELAS 4 SDN CIPEUNDEUY. - Chintia; Djuanda, Dadan; Ahmad Syahid, Aah (Universitas PGRI Palembang, 2024)
ENHANCING THE COMPREHENSION OF POETRY'S PACE BY UTILIZING INTERACTIVE POWERPOINT IN THE FOURTH-GRADE CLASS OF SDN CIPEUNDEUY. The research entitled